Karakteristik lahan budidaya kakao (Theobroma cacao L.) di distrik Manokwari Utara kabupaten Manokwari provinsi Papua Barat - Theresia Hae; Sartji Taberima; Antonius Suparno; Inna Martha Rumainum (Agrotek, 2021)
This study aims to study soil fertility status, determine land suitability status and provide recommendations for land suitability for cocoa cultivation based on land suitability evaluation in 6 (six) villages in North Manokwari District based on its slopes. The 6 (six) villages in the research location such as Pami, Mandopi, Sairo, Bremi, Yoom, and Lebau. The study lasted for approximately three (3) months, from March to May 2019. The results showed that the soil fertility status at the study site on a slope of 0-8% (SPT 1) was classified as moderately fertile. The slope of 8-15% (SPT 2) and the slope of 15-25% (SPT 3) were quite fertile. The land suitability status for SPT1 land was actually categorized as marginal (S3), but it can be upgraded to a potential land suitability class of S2 with some improvements. SPT 2 land is actually categorized as marginal (S3) and quite suitable (S2), which can be increased to potential land suitability classes S2 and S1. SPT 3 land is actually categorized according to marginal (S3) and quite suitable (S2), but can be increased to potential land suitability classes S2 and S1. Recommended land potential for cocoa plant development are on SPT 2 land with a slope of 8-15%, namely in Lebau Village, Yoom, Mandopi; and SPT 3 with a slope of 15-25%, namely Lebau, Sairo, Pami.